A retrospective analysis of the pathogens in the airways of patients with primary ciliary dyskinesia. (September 2019) - Roden, Lukas; Görlich, Dennis; Omran, Heymut; Peters, Georg; Große-Onnebrink, Jörg; Kahl, Barbara C.
Abstract: Introduction: Primary ciliary dyskinesia (PCD) is a rare genetically heterogeneous disorder of motile cilia, which leads to recurrent and chronic airway infections. Detailed information about infection causing pathogens is scarce. With this study, we aimed to determine the prevalence and susceptibility of the most common respiratory pathogens in PCD patients retrospectively in a cross-sectional and the dynamics of the microbiological diversity in a longitudinal study. Methods: Microbiological and clinical data of 106 patients between 2010 and 2016 were analysed cross-sectionally and of 28 patients longitudinally. Dynamics in microbiological diversity were assessed by calculating the mean rate of alteration (MRA). Results: Haemophilus influenzae was the most common pathogen (n = 41; 38.7%) followed by Staphylococcus aureus (n = 36; 34%), Moraxella catarrhalis (n = 18; 17%) and Pseudomonas aeruginosa (n = 16; 15.1%). Nontuberculous mycobacteria were cultured from two patients (1.9%). H. influenzae was the most prevalent pathogen in children (n = 31; 45.6%), S. aureus in adults (n = 15; 39%). Two patients were infected by methicillin-resistant S. aureus . P. aeruginosa was mostly susceptible to standard antibiotics with highest rates of resistance against fosfomycin (63.6%; 7/11). The culture of P. aeruginosa correlated negatively with age adjusted FEV1 % predicted (p = 0.04), while the MRA was positively associated with age (rho 0.411, p = 0.032). Discussion: In PCD patients, the prevalence of pathogens differed in children and adults with H. influenzae and S. aureus being the most common pathogens in children, S. aureus and P. aeruginosa in adults, respectively. Unexpectedly, the MRA increased by age. Highlights: Primary ciliary dyskinesia (PCD), a rare genetically heterogeneous disorder of motile cilia, leads to recurrent and chronic airway infections. Detailed information about infection causing pathogens is scarce. A retrospective cross-sectional analysis of 106 PCD patients and longitudinal analysis of 28 PCD was performed. Data about prevalence and dynamics of important pathogens of PCD patients are presented. Microbiological data are associated to lung function as assessed by adjusted FEV1% predicted.